Batman: Wayne family adventures. Volume four - Payne, CRC (DC Comics, 2024)
"Continuing the exciting Webtoons tale! Batman needs a break. But with new vigilante Duke Thomas living in Wayne Manor and an endless supply of adopted, fostered, and biological superhero children to manage, Bruce Wayne has his hands full"--